2014
DOI: 10.1002/jhet.2130
|View full text |Cite
|
Sign up to set email alerts
|

New Synthesis of 3,6‐Dibromophthalonitrile and Phthalocyanine Having Eight Thienyl Substituents at Peripheral α‐Positions

Abstract: 3,6‐Dibromophthalonitrile was successfully synthesized from 3,6‐dihydroxyphthalonitrile using triphenylphosphine dibromide as bromation reagent. Starting from 3,6‐dibromophthalonitrile, synthesis of 1,4,8,11,15,18,22,25‐octakis(4‐dodecylthiophen‐2‐yl)phthalocyaninatozinc(II) (ZnPc) was described. TGA demonstrated the perfect stability of ZnPc. The newly prepared ZnPc that was symmetrically substituted with thienyl substituents results in an intensively red‐shifted Q‐band. The HOMO and LUMO values of ZnPc were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…3.1. Synthesis and characterization 3,6-bis(3-hydroxypropylthio)phthalonitrile (3) was synthesized via a condensation reaction of 3,6-dibromophthalonitrile [22] with 3-mercapto propanol under very convenient conditions with a better yield than the first synthesis result (38%) (Scheme 1) [23]. This compound was prepared previously by the S N Ar reaction of 3,6-(4'-methylphenyl-sulfanyloxy) phthalonitrile with 3-mercapto-propanole.…”
Section: Resultsmentioning
confidence: 99%
“…3.1. Synthesis and characterization 3,6-bis(3-hydroxypropylthio)phthalonitrile (3) was synthesized via a condensation reaction of 3,6-dibromophthalonitrile [22] with 3-mercapto propanol under very convenient conditions with a better yield than the first synthesis result (38%) (Scheme 1) [23]. This compound was prepared previously by the S N Ar reaction of 3,6-(4'-methylphenyl-sulfanyloxy) phthalonitrile with 3-mercapto-propanole.…”
Section: Resultsmentioning
confidence: 99%
“…The starting material for the non-peripheral alkyl substituted Pc's, 3,6dihalophthalonitrile (21b), is not commercially available and though the preparation of the 3,6-dibromo- 23 and 3,6-diiodophthalonitrile 24,25 have been documented, no reports for the application thereof in the preparation of 3,6-dialkylphthalonitriles (21) could be found. We therefore decided to apply the reliable Diels Alder strategy to the synthesis of 3,6-dialkylphthalonitriles (21).…”
Section: 6-dialkylphthalonitriles (21a)mentioning
confidence: 99%
“…36 The Diels-Alder reaction of thiophene 1,1-dioxide (24) with fumaronitrile is very sluggish, though. 23,28,30,31 A theoretical study by Jursic 36 indicated the HOMO energy of thiophene 1-oxide to be higher than that of thiophene 1,1-dioxide, thus confirming it to be more electron-rich than the latter. In this regard, Thiemann and co-workers [37][38][39] reported a one-pot oxidation-cycloaddition procedure wherein BF3.OEt2 by coordinating to the S-monoxide oxygen and decreasing the nucleophilicity of the sulphur atom, prevents over-oxidation to the dioxide in the presence of meta-chloroperbenzoic acid (mCPBA).…”
Section: 6-dialkylphthalonitriles (21a)mentioning
confidence: 99%
See 1 more Smart Citation
“…The ligation-RCA produced long, randomly coiled DNA concatemers consisting of tandem repeats of target G4-forming sequence on the Qbead. The presence of a G4-specifc fluorescent label, zinc phthalocyanine (ZnPc), 49 induced the G4 formation, generating a "G4/ZnPc nanowireson-Qbead" superstructure. An array of the superstructures was readily subjected to flow cytometry, by which three targets were identified by the Qbead signals and quantified by the ZnPc signal.…”
mentioning
confidence: 99%